2021
DOI: 10.1016/j.ejphar.2021.174193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Th1 and Th2 mediated cellular and humoral immunity in patients with COVID-19 following the use of melatonin as an adjunctive treatment

Abstract: Coronavirus (SARS-CoV-2) is spreading rapidly in the world and is still taking a heavy toll. Studies show that cytokine storms and imbalances in T-helper (Th)1/Th2 play a significant role in most acute cases of the disease. A number of medications have been suggested to treat or control the disease but have been discontinued due to their side effects. Melatonin, as an intrinsic molecule, possesses pharmacological anti-inflammatory and antioxidant properties that decreases in concentration with age; as a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…In this context, a very small‐scale clinical study conducted in Iran showed promising results, halving the recovery time of COVID‐19 patients who were subjected to combinatory therapy including melatonin, compared to those not treated with melatonin. 78 Larger‐scale studies in humans and further preclinical studies in animals with mechanistic evaluations would determine the effectiveness of melatonergic therapy in COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a very small‐scale clinical study conducted in Iran showed promising results, halving the recovery time of COVID‐19 patients who were subjected to combinatory therapy including melatonin, compared to those not treated with melatonin. 78 Larger‐scale studies in humans and further preclinical studies in animals with mechanistic evaluations would determine the effectiveness of melatonergic therapy in COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanism of that suppression is not specifically known [ 68 ], it may be the result of its direct inhibition of the cytosolic oxygen sensor or related to the potent antioxidant activity of the molecule which removes the agents that stabilize HIF-1α, i.e., ROS [ 69 ]. Thus, if the prediction of Codo et al [ 64 ] is valid, which we feel it is, the inhibition of HIF-1α would contribute to a reduction in lung damage and COVID-19 severity, then the use of melatonin as a treatment of SARS-CoV-2-infected patients would be further justified [ 70 72 ].…”
Section: Melatonin/hif1α Interactionsmentioning
confidence: 99%
“…While melatonin may be useful to align circadian rhythms, it is also known for its anti-inflammatory, immunomodulatory, and antioxidant mechanisms [ 54 ]. Two recent clinical trials have noted promising results, but also point to the need for further investigation [ 55 , 56 ]. Since melatonin has a high safety profile, a low cost, and is widely available, this may represent an interesting compound to further study in the light of viral infections and vaccination.…”
Section: Discussionmentioning
confidence: 99%